Informal payments by patients, institutional trust and institutional asymmetry - Horodnic, Adrian V.; Williams, Colin C.; Ciobanu, Claudia Ioana; Druguș, Daniela (Frontiers in Psychology, 2022)
The aim of this paper is to evaluate the extent of the practice of using informal payments for accessing the services of public clinics or hospitals across Europe and to explain the prevalence of this corrupt practice using the framework of institutional theory. To achieve this, a multi-level mixed-effect logistic regression on 25,744 interviews undertaken in 2020 with patients across 27 European Union countries is conducted. The finding is that the practice of making informal payments remains a prevalent practice , although there are large disparities in the usage of this practice in different European countries. However, informal payments by patients are more likely when there is a lower institutional trust and a higher degree of asymmetry between formal and informal institutions. The resultant proposal is that policy makers need to address the institutional environment to tackle such informal payments. How this can be achieved is outlined.